The Effect of Flourishing and Workload on The Performance of Inpatient Nurses at PKU Muhammadiyah Karanganyar Hospital - Nurcahyanto, Aditiya; Rosa, Elsye Maria; Aini, Qurratul (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Nursing care is the most common health service in the hospital, so nurses' performance can significantly impact the quality and income of the hospital. When working, nurses very easy to experience pressure and stress. Understanding the flourishing of the nurse is expected to achieve a balance in her life. This study used quantitative methods with three variables. The research focus is on inpatient nurses, sampling research with the total sampling method. The study's results found that the flourishing rate was very good at 78.8%, the performance was very good at 69.7%, and the workload was very high at 49.4%. Flourishing can affect the performance of the nurse. Flourishing is expected to help nurses cultivate positive emotions and can pass them on to patients.Abstrak: Asuhan keperawatan merupakan pelayanan kesehatan yang paling banyak di Rumah Sakit. Sehingga kinerja perawat dapat berdampak besar pada mutu dan pendapatan Rumah Sakit. Saat bekerja perawat sangat mudah mengalami tekanan dan stress. Dengan memahami flourishing perawat diharapkan dapat mencapai keseimbangan kehidupannya. Penelitian ini menggunakan metode kuantitatif dengan tiga variabel. Fokus penelitian pada perawat rawat inap, pengambilan sampel penelitian dengan metode total sampling. Hasil penelitian menemukan bahwa tingkat flourishing sangat baik yaitu 78,8% dan kinerja sangat baik 69,7%, sedangkan beban kerja sangat tinggi 49,4%. Flourishing dapat mempengaruhi kinerja perawat. Flourishing diharapkan dapat membantu perawat menumbuhkan emosi-emosi positif dan dapat menularkannya kepada pasien.